P257 Understanding the effects on lung function of chest binder use in the transgender population. (15th November 2016) - Cumming, RJM; Sylvester, K; Fuld, J
Abstract : Introduction: Chest binders are garments used for compression of breast tissue by transgender individuals. Deleterious consequences of binder reported include shortness of breath with associated reduced exercise tolerance and speech difficulties; some have suggested lung function is monitored in users of chest binders. 1 We conducted a study to investigate any respiratory deficits caused by chest binders as currently used in the transgender population. Methods: We recruited 20 participants from the transgender community. All were assigned female at birth. Ages ranged from 19–47 with median age 22; 4 were current smokers and 4 had mild to moderate asthma. All were habitual users of chest binders. Participants underwent spirometry testing and measures of chest circumference and posture with and without their own binder. The order of testing with or without the binder was random. Ethics approval was granted by the University of Cambridge. Results: Table 1 shows abnormal baseline lung function. The median FEV1/FVC is abnormally high but not acutely influenced by the binder. The standard residual of all forced spirometric values was significantly (p < 0.001) below predicted values (based on sex assigned at birth); peak expiratory flow (PEF) values were also lower than predicted. There was a significant reduction in expiratory vital capacities, both SVC and FVC (p < 0.01) when the binder was on but no other significant acute change. On average chest circumference was reduced by the binder. There was no average change in thoracic kyphosis due to high variability. Conclusions: Transgender individuals using chest binders have abnormal lung function. The acute effect of wearing the binder appears to be an overall volume reduction with little other change. Abnormal lung function in the population may indicate a chronic effect of binder usage or generally poor respiratory health. However, due to the small size and timeframe of the study no control population was tested and thus a systematic error cannot be ruled out. Reference: Davies S, Papp VG, Antoni C. Voice and communication change for gender nonconforming individuals: Giving voice to the person inside. Int J Transgenderism 2015;16 :117–159.